Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Konflik Kerja Terhadap Kinerja Karyawan J&T Express Dan J&T Cargo Cabang Kras, Ngadiluwih Dan Mojo - Ani Setyawati; Indah Yuni Astuti; Ririn Wahyu Arida (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
An employee's performance can affect the company's success in competing with its competitors to achieve its goals. However, there are several factors that can affect the rise and fall of employee performance. This study aims to determine the effect of the work environment, work discipline, and work conflict on employee performance. This study uses quantitative methods to evaluate the relationship between variables. Data were obtained through questionnaire results analyzed using SPSS Version 25 software. The total questionnaire data was 31 respondents from the number of J&T Express and J&T Cargo employees at the Kras, Ngadiluwih, and Mojo Branches. The results of this study prove that the work environment, work discipline, and work conflict have a partial and simultaneous effect on employee performance. The coefficient of determination supports the results of this study with a percentage level of 81.9% of variable (X) affecting variable (Y). Also, the work environment successfully dominates its influence on employee performance.